Identification of a Subtype-Selective Allosteric Inhibitor of GluN1/GluN3 NMDA Receptors - Zeng, Yue; Zheng, Yueming; Zhang, Tongtong; Ye, Fei; Zhan, Li; Kou, Zengwei; Zhu, Shujia; Gao, Zhaobing (Frontiers in Pharmacology, 2022)
N-methyl-D-aspartate receptors (NMDARs) are Ca2+-permeable ionotropic glutamate receptors (iGluRs) in the central nervous system and play important roles in neuronal development and synaptic plasticity. Conventional NMDARs, which typically comprise GluN1 and GluN2 subunits, have different biophysical properties than GluN3-containing NMDARs: GluN3-containing NMDARs have smaller unitary conductance, less Ca2+-permeability and lower Mg2+-sensitivity than those of conventional NMDARs. However, there are very few specific modulators for GluN3-containing NMDARs. Here, we developed a cell-based high-throughput calcium assay and identified 3-fluoro-1,2-phenylene bis (3-hydroxybenzoate) (WZB117) as a relatively selective inhibitor of GluN1/GluN3 receptors. The IC50 value of WZB117 on GluN1/GluN3A receptors expressed in HEK-293 cells was 1.15 ± 0.34 μM. Consistently, WZB117 exhibited strong inhibitory activity against glycine-induced currents in the presence of CGP-78608 but only slightly affected the NMDA-, KA- and AMPA-induced currents in the acutely isolated rat hippocampal neurons. Among the four types of endogenous currents, only the first one is primarily mediated by GluN1/GluN3 receptors. Mechanistic studies showed that WZB117 inhibited the GluN1/GluN3A receptors in a glycine-, voltage- and pH-independent manner, suggesting it is an allosteric modulator. Site-directed mutagenesis and chimera construction further revealed that WZB117 may act on the GluN3A pre-M1 region with key determinants different from those of previously identified modulators. Together, our study developed an efficient method to discover modulators of GluN3-containing NMDARs and characterized WZB117 as a novel allosteric inhibitor of GluN1/GluN3 receptors.